Analysis and Design of a Fully Submerged Underground Water Tank Using the Principle of Beam on Elastic Foundations (2015)
The basic requirement in the design of reinforced water tank is to ensure it is crack free. This research studied the analysis and design of a fully submerged underground reinforced concrete water tank using the principle of beam on elastic foundations. To achieve this, a Microsoft Excel Spreadsheet Design and Analysis Program (MESDAPro) was generated for quick assessment of various moments of the tank, geometrical features and soil conditions for both full and empty conditions of the tank. It was observed that the wall moments, moment at base of wall and base slab moment decreases with increase in soil sub-grade modulus at constant capacity, height and breadth of the tank. However, wall moments, moment at base of wall and base slab moment increases with increase in height of the tank at constant value of sub-grade modulus, tank capacity and breadth. In all the examined cases, the moments obtained are higher when the tank is considered empty than when considered full